Diversity and cellulolytic activity of culturable bacteria isolated from the gut of higher termites (Odontotermes sp.) in eastern Thailand - Parima Boontanom; Aiya Chantarasiri (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Boontanom P, Chantarasiri A. 2021. Diversity and cellulolytic activity of culturable bacteria isolated from the gut of higher termites (Odontotermes sp.) in eastern Thailand. Biodiversitas 22: 3349-3357. Cellulolytic bacteria are vital symbionts associated with the gut of all higher termites. Odontotermes termites are a higher termite widely found in Thailand. However, information concerning the diversity of cellulolytic bacteria in this termite gut remains inadequate. The aim of this study is to isolate and identify the culturable cellulolytic bacteria from the Odontotermes gut collected from eastern Thailand. The crude cellulases produced from the most active cellulolytic bacterium were further characterized. Thirty-two cellulolytic bacteria were isolated and subsequently classified by PCR-RFLP of the 16S rRNA gene. A total of 10 different RFLP patterns were obtained belonging to five bacterial genera, namely Acinetobacter, Bacillus, Citrobacter, Paenibacillus, and Serratia. The B. cereus strain TWV503 was considered to be the most active cellulolytic bacterium based on the CMC agar method. B. cereus strain TWV503 showed CMCase activity at 2.190 ± 0.063 U/mL of CMCase and 0.276 ± 0.031 U/mL of FPase. The optimum temperature and pH for CMCase activity were 50°C and the neutral pH ranging from 7.0 to 8.0, respectively. CMCase activity remained stable at up to 70°C and neutral pH ranging from 7.0 to 8.0 for 24 hours of incubation. This study revealed novel information related to cellulolytic bacteria isolated from the gut of Odontotermes termites collected from Thailand.